Fracture Initiation Model of Shale Fracturing Based on Effective Stress Theory of Porous Media - Yuwei Li; Dan Jia (Geofluids)
Unconventional oil and gas are important resources of future energy supply, and shale gas is the focus of the development of unconventional resources. Shale is a special kind rock of porous medium, and an orderly structure of beddings aligned in the horizontal direction where causing the strong elastic anisotropy of shale is easy. A new model has been established to calculate the fracture initiation pressure with the consideration of mechanical characteristics of shale and the anisotropic tensile strength when judging rock failure. The fracture initiation model established in this paper accurately reflects the stress anisotropy and matches well with the actual situation in porous media. Through the sensitivity analysis, the results show that σv/σH, Ev/EH, υv/υH, m/s, and A/B have a certain impact on the tangential stress when the circumferential angle changes, and there is a positive relationship between the initiation pressure and the above sensitive factors except for A/B. The results can provide a valuable and effective guidance for the prediction of fracture initiation pressure and fracture propagation mechanism under special stratum conditions of shale.